2021
DOI: 10.3390/ijms22063272
|View full text |Cite
|
Sign up to set email alerts
|

A Mitocentric View of the Main Bacterial and Parasitic Infectious Diseases in the Pediatric Population

Abstract: Infectious diseases occur worldwide with great frequency in both adults and children. Both infections and their treatments trigger mitochondrial interactions at multiple levels: (i) incorporation of damaged or mutated proteins to the complexes of the electron transport chain, (ii) mitochondrial genome (depletion, deletions, and point mutations) and mitochondrial dynamics (fusion and fission), (iii) membrane potential, (iv) apoptotic regulation, (v) generation of reactive oxygen species, among others. Such alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 163 publications
(245 reference statements)
0
1
0
Order By: Relevance
“…The World Health Organization (WHO) has reported that microbial diseases (both from bacteria and fungi) are a leading cause of death in humans [ 1 ], which can be transmitted directly or indirectly from one individual to another, and that bacterial resistance causes more than 10 million deaths per year [ 2 , 3 , 4 , 5 ]. The microorganisms of greatest interest that cause infectious diseases in humans are bacteria such as Salmonella typhi (causing typhoid fever), Staphylococcus aureus (causing skin infections, sometimes pneumonia, endocarditis, and osteomyelitis), Streptococcus pneumoniae (causing pneumonia), among others [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has reported that microbial diseases (both from bacteria and fungi) are a leading cause of death in humans [ 1 ], which can be transmitted directly or indirectly from one individual to another, and that bacterial resistance causes more than 10 million deaths per year [ 2 , 3 , 4 , 5 ]. The microorganisms of greatest interest that cause infectious diseases in humans are bacteria such as Salmonella typhi (causing typhoid fever), Staphylococcus aureus (causing skin infections, sometimes pneumonia, endocarditis, and osteomyelitis), Streptococcus pneumoniae (causing pneumonia), among others [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%